Positive electrode material, preparation method thereof, positive electrode plate and sodium ion battery
By recycling and utilizing waste lithium iron phosphate positive electrode material, a high-purity and excellent morphology sodium iron phosphate positive electrode material is prepared, which solves the problems of improving the performance and resource utilization of the positive electrode material in the prior art, and achieves the high energy density and long cycle stability of sodium ion batteries.
Patent Information
- Application Number
- CN202411900736.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to prepare a sodium ion battery cathode material with excellent morphology and good electrochemical activity and stability based on the resource utilization of waste lithium iron phosphate.
A positive electrode material, including sodium ferric phosphate fluoropyrophosphate, is provided. By recycling and utilizing waste lithium iron phosphate positive electrode material, pretreated, adsorbed and calcined in a specific process flow, to prepare a positive electrode material with high purity and excellent morphology.
The preparation of positive electrode materials with high purity and excellent morphology has been achieved, which significantly improves the energy density, cycle stability and rate performance of sodium ion batteries, reduces production costs, and has significant environmental benefits.
Smart Images

Figure CN119695147A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a positive electrode material, a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] As the shortage of lithium resources has constrained the development of lithium-ion batteries, sodium-ion batteries are currently considered to be one of the powerful alternatives, especially in the field of power batteries for new energy vehicles. However, the performance of the most commonly used iron-based sodium-ion battery cathode materials, especially the electrochemical activity and stability, still has a lot of room for improvement. It is necessary to have more precise composition matching, purity optimization and morphology design.
[0003] At the same time, the resource utilization and recycling of discarded lithium iron phosphate has attracted more and more attention as the amount of scrapped lithium iron phosphate batteries has increased dramatically. For discarded lithium iron phosphate, the conventional chemical treatment method is to chemically dissolve it, then remove impurities, remove iron and phosphorus, and then extract the lithium. This process has the disadvantages of high cost, low added value of products, especially the added value of phosphorus iron elements is very low, and the amount of wastewater generated is large, and there is also a low utilization rate of elements. Although there are methods in the prior art for preparing lithium iron phosphate positive electrode materials using waste lithium iron phosphate batteries, the overall route has a poor impurity removal effect, and the resulting positive electrode materials generally have more impurities and poor performance.
[0004] For the above reasons, how to provide a sodium ion battery positive electrode material with high phase purity and excellent morphology based on the resource utilization of waste lithium iron phosphate so that it exhibits high electrochemical activity and stability is one of the important technical problems that need to be solved in this field. Summary of the invention
[0005] The main purpose of the present application is to provide a positive electrode material, a preparation method thereof, a positive electrode plate and a sodium ion battery, so as to solve the problem that it is difficult in the prior art to prepare a sodium ion battery positive electrode material with excellent morphology, electrochemical activity and stability based on the resource utilization of waste lithium iron phosphate.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode material, which includes sodium ferric phosphate fluoropyrophosphate, wherein the molecular formula of the sodium ferric phosphate fluoropyrophosphate is Na m Fe3(PO4) p (P2O7) q F w , among which, 5.02≤m≤5.05, 4.02≤p+2q≤4.05, 0.5p≤q≤0.55p, 1.01≤w≤1.05, 1.87≤p≤2.05.
[0007] The cathode material provided in the present application has a unique chemical element composition, and can be used as an excellent cathode material to significantly improve the energy density of the corresponding sodium ion battery, while allowing the battery to maintain good cycle stability and excellent rate performance. In particular, the introduction of fluorine, which has a stronger electronegativity, can increase the voltage platform of the cathode material, and at the same time play a role in anion doping, thereby further improving the ionic conductivity of the resulting cathode material.
[0008] Furthermore, the positive electrode material also includes sodium iron phosphate, and the mass fraction of sodium iron phosphate in the positive electrode material is ≤1.1%. By controlling the content of sodium iron phosphate in the positive electrode material, the electrochemical performance of the positive electrode material can be further optimized, because sodium iron phosphate is an electrochemically inert substance, and reducing its content can improve capacity, cycle life and safety. More preferably, in the XRD spectrum of the positive electrode material, the main peak height H1 of sodium iron phosphate fluoropyrophosphate and the main peak height H2 of the sodium iron phosphate impurity satisfy: H2 / H1≤1.5%. The above-mentioned positive electrode material provided in the present application exhibits superior electrochemical properties due to its high purity characteristics, and when applied to sodium ion batteries, it exhibits higher capacity and stronger long-cycle stability.
[0009] In some preferred embodiments, the sphericity of the positive electrode material is 0.94 to 0.99. The inventors have optimized the sphericity of the positive electrode material through a large number of experiments, so that the positive electrode material has a nearly circular microscopic morphology, thereby showing better electrode contact performance. At the same time, the positive electrode material with high sphericity has a shorter and more uniform migration distance of sodium ions, better electrolyte infiltration, and better gradation between particles (because of better fluidity, it is convenient for large and small particles to embed each other), which effectively improves the charging efficiency and discharge efficiency of the sodium ion battery in which it is located.
[0010] The second aspect of the present application provides a method for preparing a positive electrode material, comprising: providing discarded lithium iron phosphate positive electrode material; dissolving the discarded lithium iron phosphate positive electrode material to obtain a pretreated filter residue; mixing the pretreated filter residue with a pyrophosphoric acid solution to obtain a first filtrate; mixing the first filtrate with a precipitant to obtain a second filtrate; mixing the second filtrate with a pH regulator, a ferrous source, and an oxidant to obtain a third filtrate and a third filter residue; performing adsorption treatment on the third filtrate to obtain an adsorption residual liquid; mixing the adsorption residual liquid, the third filter residue, a sodium source, a phosphorus source, and a fluorine source to obtain a mixed slurry; and grinding, drying, and calcining the mixed slurry in sequence to obtain a positive electrode material.
[0011] The above-mentioned preparation method of the present application recycles discarded lithium iron phosphate positive electrode materials to prepare the positive electrode materials as described above, which not only effectively reduces the production cost of the positive electrode materials, but also realizes the recycling of waste battery materials, and has significant environmental benefits. The prepared positive electrode material has excellent electrochemical properties, can significantly improve the energy density and cycle stability of sodium ion batteries, and provides strong support for the commercial application of sodium ion batteries. At the same time, the obtained positive electrode material has stable performance and can meet the application requirements of sodium ion batteries in large-scale energy storage systems.
[0012] Further, in the step of dissolving the discarded lithium iron phosphate positive electrode material to obtain the pre-treated filter residue, an alkaline agent is used to dissolve the discarded lithium iron phosphate positive electrode material; and / or, the step of mixing the pre-treated filter residue with a pyrophosphoric acid solution to obtain a first filtrate includes: mixing the pre-treated filter residue with a pyrophosphoric acid solution, and after a first reaction time at a first reaction temperature, subjecting the mixture to a first solid-liquid separation treatment to obtain a first filtrate; and / or, the step of mixing the first filtrate with a precipitant to obtain a second filtrate includes: mixing the first filtrate with a precipitant, and after a second reaction time at a second reaction temperature, subjecting the mixture to a second solid-liquid separation treatment to obtain a second filtrate; and / or, the step of mixing the second filtrate with a pH regulator, a ferrous source, and an oxidant to obtain a third filtrate and a third filter residue includes: mixing the second filtrate with a pH regulator, a ferrous source, and an oxidant, and after reaching a third reaction endpoint pH value, subjecting the mixture to a third solid-liquid separation treatment for a third reaction time to obtain a third filtrate and a third filter residue; and / or, the step of adsorption treatment includes: treating the third filtrate by adsorption using an ion exchange resin.
[0013] On the basis of the above process flow, the specific steps are further optimized to more accurately control the reaction conditions in the recycling and reprocessing process, such as reaction temperature, time and end point pH value, so as to more effectively remove impurities in waste battery materials and significantly improve the purity and electrochemical properties of the final positive electrode material, making it more suitable for high energy density sodium ion batteries.
[0014] Furthermore, the mass ratio of the alkaline agent to the discarded lithium iron phosphate positive electrode material is (3-5):1; in the first filtrate, the molar ratio of phosphate to pyrophosphate is 1:(0.45-0.49); the ratio of the molar amount of the precipitant to the sum of the molar amounts of nickel ions, cobalt ions, copper ions and zinc ions in the first filtrate is (1.2-1.5):1; the ratio of the molar amount of iron in the ferrous source to the molar amount of pyrophosphate in the second filtrate is (0.95-0.98):1; in the mixed slurry, the molar ratio of Na, Fe, P and F is (5.02-5.05):3:(4.02-4.05):(1.01-1.05).
[0015] By optimizing the mass relationship and the amount ratio of substances in each step, the recovery rate of waste iron-lithium positive electrode materials can be further improved. At the same time, the purity of the obtained positive electrode materials can be optimized, and their electrochemical properties can be improved, making their application in sodium-ion batteries more extensive.
[0016] Furthermore, the concentration of the alkali agent is 3mol / L to 5mol / L; the concentration of the pyrophosphoric acid solution is 3mol / L to 5mol / L; the mass fraction of Al in the pre-treated filter residue is less than 0.1%; and the Li + Concentration <100ppm.
[0017] During the preparation process, optimizing the concentration of the raw materials used and controlling the component content of the resulting product are beneficial to the prepared positive electrode material having high purity and stability, reducing the performance degradation of the positive electrode material during the charge-discharge process, and extending the service life of the corresponding sodium-ion battery.
[0018] Furthermore, the first reaction temperature is 70°C to 90°C, and the first reaction time is 1h to 2h; the second reaction temperature is 40°C to 60°C, and the second reaction time is 30min to 60min; the third reaction endpoint pH value is 2.8 to 3.2, and the third reaction time is 30min to 60min; the calcination temperature is 550°C to 650°C, and the calcination insulation time is 10h to 13h.
[0019] By controlling the reaction conditions in the above steps, it is beneficial to more significantly optimize the crystal structure and morphology of the resulting positive electrode material, thereby improving its electrochemical performance and ultimately improving the cycle performance and energy density of the corresponding sodium ion battery.
[0020] Furthermore, the alkaline agent is sodium hydroxide solution; the precipitant is selected from one or more of sodium sulfide, sodium bisulfide and sodium N,N-dimethyldithiocarbamate; the pH adjuster is selected from one or more of sodium hydroxide, ammonia water, ammonium bicarbonate and ammonium carbonate; the ferrous source is selected from one or more of ferrous acetate, ferrous citrate and ferrous gluconate; the oxidant is selected from one or more of hydrogen peroxide, oxygen and ozone.
[0021] On the basis of the above-mentioned reaction step settings, reaction conditions and the optimization of the relationship between the amounts, suitable chemical reagents are further selected for different steps as above, so as to further optimize the preparation process, comprehensively improve the various properties of the positive electrode material, and improve the electrical performance of the corresponding sodium ion battery.
[0022] The third aspect of the present application provides a positive electrode sheet, which includes the above-mentioned positive electrode material, or the positive electrode material prepared by the above-mentioned method for preparing the positive electrode material. Because the positive electrode material obtained in the present application has a better morphology, higher phase purity, and fewer impurities, the corresponding positive electrode sheet also has better electrochemical performance.
[0023] The fourth aspect of the present application provides a sodium ion battery, which includes the above-mentioned positive electrode plate. Because the above-mentioned sodium iron fluoropyrophosphate positive electrode material obtained in the present application has good microscopic morphology and extremely high phase purity, when it is used as a positive electrode plate component in a sodium ion battery, the obtained sodium ion battery also has comprehensively improved electrochemical performance, especially the first discharge capacity and cycle stability.
[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is the SEM result of the positive electrode material obtained in Example 1;
[0027] Figure 2 The XRD patterns of Examples 1 to 3 are shown in FIG. DETAILED DESCRIPTION
[0028] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0030] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0031] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0032] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0033] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0034] In the description of the embodiments of the present application, unless otherwise specified, the solvent used in “solution”, “filtrate”, etc. is water, preferably at least one of distilled water, deionized water, pure water, and ultrapure water.
[0035] As described in the background technology, the prior art has the problem that it is difficult to prepare a sodium ion battery positive electrode material with excellent morphology, electrochemical activity and stability based on the resource utilization of waste lithium iron phosphate. In order to solve the above technical problems, the first aspect of the present application provides a positive electrode material, which includes sodium ferric phosphate fluoropyrophosphate, and the molecular formula of sodium ferric phosphate fluoropyrophosphate is Na m Fe3(PO4) p (P2O7) q F w , among which, 5.02≤m≤5.05, 4.02≤p+2q≤4.05, 0.5p≤q≤0.55p, 1.01≤w≤1.05, 1.87≤p≤2.05.
[0036] The cathode material provided in the present application has a unique chemical element composition, and can be used as an excellent cathode material to significantly improve the energy density of the corresponding sodium ion battery, while allowing the battery to maintain good cycle stability and excellent rate performance. In particular, the introduction of fluorine, which has a stronger electronegativity, can increase the voltage platform of the cathode material, and at the same time play a role in anion doping, thereby further improving the ionic conductivity of the resulting cathode material.
[0037] Further, 5.02≤m≤5.05, 2.0≤p≤2.01, 1.01≤q≤1.02, 1.01≤w≤1.05.
[0038] Furthermore, the molecular formula of sodium ferric fluoropyrophosphate in the positive electrode material is Na 5.03 Fe3(PO4) 2.0 (P2O7) 1.02 F 1.03 、Na 5.02 Fe3(PO4) 2.0 (P2O7) 1.01 F 1.01 Or Na 5.05 Fe3(PO4) 2.01 (P2O7) 1.01 F 1.05 .
[0039] Furthermore, the positive electrode material also includes sodium iron phosphate, and the mass fraction of sodium iron phosphate in the positive electrode material is ≤1.1%, specifically 0.14%, 0.21%, 0.23%, 0.24%, 0.25%, 0.46%, 0.98%; preferably 0.1% to 1.01%; more preferably 0.10% to 0.5%; and even more preferably 0.10% to 0.23%. By controlling the content of sodium iron phosphate in the positive electrode material, the electrochemical performance of the positive electrode material can be further optimized, and the capacity, cycle life and safety can be improved.
[0040] Further, in the XRD spectrum of the positive electrode material, the main peak height H1 of sodium ferric phosphate fluoropyrophosphate and the main peak height H2 of the sodium ferric phosphate impurity meet: H2 / H1≤1.5%, specifically 0.2%, 0.3%, 0.4%, 0.42%, 0.45%, 0.46%, 0.57%, 1.22%, preferably 0.2% to 1.22%, more preferably 0.2% to 0.36%, and more preferably 0.2% to 0.4%. The above-mentioned positive electrode material provided in the present application exhibits superior electrochemical properties due to its high purity characteristics, and when applied to sodium ion batteries, it exhibits higher capacity and stronger long-cycle stability.
[0041] In some preferred embodiments, the sphericity of the positive electrode material is 0.94 to 0.99, specifically 0.945, 0.946, 0.961, 0.968, 0.969, 0.972, 0.974, 0.985, preferably 0.945 to 0.99, more preferably 0.96 to 0.99, and even more preferably 0.97 to 0.99. The inventors have optimized the sphericity of the positive electrode material through a large number of experiments, so that the positive electrode material has a nearly circular microscopic morphology, thereby showing better particle contact performance and electrolyte wettability, and effectively improving the charge and discharge efficiency of the sodium ion battery in which it is located.
[0042] Furthermore, the powder resistivity of the positive electrode material is 30 Ω·cm to 76 Ω·cm, such as 32 Ω·cm, 33 Ω·cm, 56 Ω·cm, 59 Ω·cm, 63 Ω·cm, 65 Ω·cm, 69 Ω·cm, preferably 30 Ω·cm to 65 Ω·cm, more preferably 30 Ω·cm to 60 Ω·cm. The specific surface area is 12.0 m 2 / g~17.5m 2 / g, for example 12.1m 2 / g, 12.3m 2 / g, 12.7m 2 / g, 12.9m 2 / g, 16.8m 2 / g, 17.3m 2 / g. The compacted density is 2.15g / mL to 2.25g / mL, such as 2.15g / mL, 2.16g / mL, 2.17g / mL, 2.20g / mL, 2.21g / mL, 2.22g / mL, 2.23g / mL, and 2.25g / mL.
[0043] Furthermore, the positive electrode material also includes carbon element, and the mass fraction of carbon element in the positive electrode material is 1.54% to 2.2%, for example, it can be 1.56%, 1.59%, 1.61%, 1.62%, 1.63%, 2.14%, 2.19%, etc.
[0044] Furthermore, the positive electrode material includes a core and a carbon coating layer, the carbon coating layer is coated on the surface of the core, and the core includes sodium ferric phosphate fluoropyrophosphate, or the core includes sodium ferric phosphate fluoropyrophosphate and sodium ferric phosphate.
[0045] Furthermore, the mass fraction of the carbon coating layer in the positive electrode material is 1.54% to 2.2%, for example, it can be 1.56%, 1.59%, 1.61%, 1.62%, 1.63%, 2.14%, 2.19%, etc.
[0046] Furthermore, at 25°C, the first charge specific capacity of the positive electrode material at a 0.2C rate is greater than or equal to 112mAh / g, preferably 112mAh / g to 122mAh / g, and more preferably 115mAh / g to 122mAh / g. For example, it can be 112.4mAh / g, 113.5mAh / g, 115.4mAh / g, 118.2mAh / g, 118.5mAh / g, 118.9mAh / g, 120.1mAh / g, 120.4mAh / g, 121.7mAh / g, etc.
[0047] Furthermore, at 25°C, the first discharge specific capacity of the positive electrode material at a 0.2C rate is greater than or equal to 103 mAh / g, preferably 103 mAh / g to 114 mAh / g, and more preferably 106 mAh / g to 114 mAh / g. For example, it can be 103.2 mAh / g, 104.1 mAh / g, 106.3 mAh / g, 107.2 mAh / g, 109.6 mAh / g, 110.3 mAh / g, 110.6 mAh / g, 111.8 mAh / g, 113.4 mAh / g, etc.
[0048] Furthermore, at 25°C, the first discharge median voltage of the positive electrode material at a 0.2C rate is greater than or equal to 3.18V, preferably 3.15V to 3.35V, and more preferably 3.2V to 3.32V. For example, it can be 3.18V, 3.21V, 3.23V, 3.25V, 3.26V, 3.27V, 3.32V, etc.
[0049] Furthermore, at 25°C, the first discharge specific capacity of the positive electrode material at a 1C rate is greater than or equal to 101mAh / g, preferably 101mAh / g to 110mAh / g, and more preferably 105mAh / g to 110mAh / g. For example, it can be 101.8mAh / g, 103.6mAh / g, 105.2mAh / g, 106.8mAh / g, 107.5mAh / g, 108.1mAh / g, 108.6mAh / g, 109.1mAh / g, 109.5mAh / g, etc.
[0050] Furthermore, at 25°C, the capacity retention rate of the positive electrode material after 500 charge-discharge cycles at a 1C rate is greater than or equal to 97.5%, preferably 97.5% to 99%, more preferably 98% to 99%, for example, it can be 97.5%, 97.6%, 98%, 98.3%, 98.6%, 98.7%, 98.9%, etc.
[0051] In some embodiments, the above-mentioned first charge specific capacity, first discharge specific capacity, and first discharge median voltage of the positive electrode material are obtained by preparing a positive electrode sheet having the positive electrode material, assembling the positive electrode sheet to form a button battery, and testing it.
[0052] The positive electrode plate includes a positive electrode active material, a binder and a conductive agent. The positive electrode active material is a lithium supplement as described above. The binder is preferably PVDF (polyvinylidene fluoride), and other adhesive materials suitable for positive electrode plates can also be used. The conductive agent is preferably a carbon conductive material, such as conductive carbon black (SP) and the like. The above-mentioned positive electrode active material, binder, and conductive agent are proportioned in a suitable mass ratio, and an aluminum sheet is used as a current collector. The mass ratio of the positive electrode active material, binder, and conductive agent of the prepared positive electrode plate can be 85:7:8, and the compacted density of the mixture of the positive electrode active material, binder, and conductive agent can be 2.2g / mL.
[0053] The second aspect of the present application provides a method for preparing a positive electrode material, comprising: providing discarded lithium iron phosphate positive electrode material; dissolving the discarded lithium iron phosphate positive electrode material to obtain a pretreated filter residue; mixing the pretreated filter residue with a pyrophosphoric acid solution to obtain a first filtrate; mixing the first filtrate with a precipitant to obtain a second filtrate; mixing the second filtrate with a pH regulator, a ferrous source, and an oxidant to obtain a third filtrate and a third filter residue; performing adsorption treatment on the third filtrate to obtain an adsorption residual liquid; mixing the adsorption residual liquid, the third filter residue, a sodium source, a phosphorus source, and a fluorine source to obtain a mixed slurry; and grinding, drying, and calcining the mixed slurry in sequence to obtain a positive electrode material.
[0054] The above-mentioned preparation method of the present application recycles discarded lithium iron phosphate positive electrode materials to prepare the positive electrode materials as described above, which not only effectively reduces the production cost of the positive electrode materials, but also realizes the recycling of waste battery materials, and has significant environmental benefits. The prepared positive electrode material has excellent electrochemical properties, can significantly improve the energy density and cycle stability of sodium ion batteries, and provides strong support for the commercial application of sodium ion batteries. At the same time, the obtained positive electrode material has stable performance and can meet the application requirements of sodium ion batteries in large-scale energy storage systems.
[0055] Furthermore, in the step of dissolving the discarded lithium iron phosphate positive electrode material to obtain the pre-treated filter residue, an alkaline agent is used to dissolve the discarded lithium iron phosphate positive electrode material.
[0056] Furthermore, the step of mixing the pretreated filter residue with the pyrophosphoric acid solution to obtain the first filtrate includes: mixing the pretreated filter residue with the pyrophosphoric acid solution, reacting at a first reaction temperature for a first reaction time, and performing a first solid-liquid separation treatment to obtain the first filtrate.
[0057] Furthermore, the step of mixing the first filtrate with the precipitant to obtain the second filtrate includes: mixing the first filtrate with the precipitant, reacting at a second reaction temperature for a second time, and performing a second solid-liquid separation treatment to obtain the second filtrate.
[0058] Furthermore, the step of mixing the second filtrate with a pH regulator, a ferrous source, and an oxidant to obtain a third filtrate and a third filter residue includes: mixing the second filtrate with a pH regulator, a ferrous source, and an oxidant, and after reaching a third reaction endpoint pH value, subjecting the mixture to a third reaction time, and subjecting the mixture to a third solid-liquid separation treatment to obtain a third filtrate and a third filter residue.
[0059] Furthermore, the step of adsorption treatment includes: using ion exchange resin to adsorb and treat the third filtrate.
[0060] The above method provided by the present application can effectively utilize the iron, phosphorus and other elements in the discarded lithium iron phosphate positive electrode material, and at the same time utilize the sodium element therein, to obtain a positive electrode material for sodium ion batteries with relatively high added value and excellent performance, with small amount of sewage generated and good environmental protection. Specifically: In the alkaline agent dissolution process, the aluminum element is mainly removed by the alkaline agent. Taking NaOH as an example, the following reaction occurs: NaOH+Al+H2O→NaAlO2+H2. The remaining pre-treated filtrate obtained by filtration is mainly a sodium-containing solution, to which pyrophosphate is added. The pyrophosphate ion has a strong coordination and is very acidic, so it is easier to dissolve lithium iron phosphate, while other impurities such as carbon are filtered out because they are insoluble. At the same time, since no oxidant is added in the alkaline dissolution step of the present application, some inactive metals, such as copper alone, are not easily dissolved and are therefore easily filtered out. In this process, the following reactions mainly occur: LiFePO4+0.5H4P2O7→Li + +Fe 2+ +H2PO4 2- +0.5P2O7 4-. The first filtrate obtained by filtering the first reaction liquid mainly contains elements such as lithium, iron, and phosphorus, to which a precipitant (such as sodium sulfide, sodium bisulfide, sodium N,N-dimethyldithiocarbamate, etc.) is added to remove heavy metals in the first filtrate. The precipitant is selected from the above-mentioned sulfide, because heavy metals such as nickel, cobalt, copper, zinc ions will react with sulfur ions to obtain sulfide precipitates that are insoluble in water, and the pH value when the precipitation is produced is relatively low. At the same time, because the reducing property of the sulfide can reduce a small amount of trivalent iron ions, it avoids ferrous iron oxidation to generate ferric phosphate precipitation, which is beneficial to reduce the loss of iron and phosphorus. After the first filtrate reacts with the precipitant, a second reaction liquid is obtained, and the second reaction liquid is filtered to obtain a second filtrate from which heavy metals have been removed. Add a pH regulator (such as sodium hydroxide, ammonia, ammonium bicarbonate and ammonium carbonate, etc.), a ferrous source (such as ferrous acetate, ferrous citrate, ferrous gluconate) and an oxidant (such as hydrogen peroxide, oxygen, ozone) to the second filtrate to react and obtain ferric phosphate / ferrous phosphate and ferric pyrophosphate / ferrous pyrophosphate, and precipitate anions such as iron, phosphate and pyrophosphate in the second filtrate to obtain a third filter residue, thereby separating it from the lithium ions in the third filtrate (containing a lithium solution, in which the cations in the solution are mainly lithium ions), providing a basis for the subsequent adsorption and recovery of the lithium element. The adsorption residual liquid obtained by further adsorbing and recovering lithium ions from the third filtrate is mixed with the third filter residue, and the third filter residue is used as an iron source, and further supplemented with a sodium source, a phosphorus source and a fluorine source to prepare sodium fluoropyrophosphate iron phosphate as a positive electrode material.
[0061] Compared with the traditional preparation process, the above-mentioned recovery preparation method provided in the present application has a shorter process and a higher recovery rate of each element. In the aqueous solution formed by the third filtrate, the mixture of sodium, iron and phosphorus elements is more uniform than that of the solid phase method. The final positive electrode material has a better morphology, higher purity and better performance.
[0062] In particular, in the above method provided in the present application, pyrophosphoric acid is used for the dissolution process of lithium iron phosphate, which has stronger acidity and can be used at a higher concentration than phosphoric acid (the mass fraction of pyrophosphoric acid in pyrophosphoric acid solution can reach 95%, while the mass fraction of phosphoric acid in phosphoric acid solution is generally only 80%). At the same time, pyrophosphoric acid can provide pyrophosphate for the positive electrode material obtained in the present application, which is conducive to fewer impurities, higher purity and higher phase purity of the positive electrode material. Compared with some solid phase processes, that is, processes for converting phosphate to prepare sodium iron pyrophosphate, the positive electrode material prepared in the present application has a higher purity. Because the process of converting phosphate to pyrophosphate needs to occur completely at a certain temperature, otherwise a certain amount of electrochemically inactive impurity sodium iron phosphate phase will be produced, resulting in a high impurity phase and low electrical performance of the final positive electrode material product. As mentioned above, the present application does not require the conversion of phosphate and pyrophosphate, thereby avoiding the generation of sodium iron phosphate impurity phase, and the resulting positive electrode material has lower impurities, higher phase purity, and better electrochemical performance.
[0063] At the same time, by using pyrophosphoric acid to dissolve lithium iron phosphate, anions can be fully utilized without generating other impurities, which is beneficial to avoid the increase in cost and the reduction in element recovery rate caused by the separation of other impurities. In addition, it can effectively avoid the generation of other wastes, has good environmental protection, and has a high recovery rate of each element. The purity of the positive electrode material obtained by re-calcining is also correspondingly higher, and the electrochemical performance is excellent.
[0064] Compared with the traditional process, that is, first preparing lithium iron phosphate waste into iron phosphate and lithium carbonate, and then mixing the iron phosphate with a sodium source for sintering, the above process provided by the present application is shorter, lower in cost, generates less wastewater, and the performance of the resulting positive electrode material is also better.
[0065] Furthermore, when the pH adjuster is sodium hydroxide, the concentration of the sodium hydroxide solution is preferably 5 mol / L to 10 mol / L.
[0066] Furthermore, the ferrous source may be mixed with the second filtrate in the form of a solution, and the concentration of the ferrous element in the ferrous source is preferably 1.5 mol / L to 2.5 mol / L.
[0067] Furthermore, the oxidant is selected from at least one of hydrogen peroxide, oxygen and ozone.
[0068] Furthermore, the concentration of the alkaline solution used for alkaline dissolution is 3 mol / L to 5 mol / L; the mass ratio of the alkaline solution to the waste lithium iron phosphate positive electrode material is (3 to 5): 1, which is beneficial to effectively improve the dissolution efficiency of aluminum in the waste lithium iron phosphate positive electrode material, reduce the generation of by-products, and thus improve the purity of the obtained positive electrode material.
[0069] Furthermore, in the pre-treated filter residue, the mass fraction of Al element is less than 0.1%.
[0070] Furthermore, the preparation method of the positive electrode material also includes introducing CO2 into the pretreatment filtrate to obtain aluminum hydroxide. That is, after the aluminum element is leached out by an alkali agent, carbon dioxide is introduced into the pretreatment filtrate, and while further reducing the impurities in the pretreatment filtrate, a small amount of aluminum therein is converted into aluminum hydroxide precipitate. The aluminum hydroxide precipitate can be used as a catalyst carrier to realize its resource utilization. The reaction occurring in this process is: 2NaAlO2+CO2+3H2O→2Al(OH)3+Na2CO3.
[0071] Furthermore, the concentration of the pyrophosphoric acid solution is 3 mol / L to 5 mol / L. The coordination and acidity of the pyrophosphoric acid solution at this concentration are more suitable, which is conducive to efficiently dissolving lithium iron phosphate and achieving effective element extraction.
[0072] Furthermore, the reaction temperature of the first reaction is 70° C. to 90° C., and the reaction time is 1 h to 2 h, so as to dissolve the lithium iron phosphate more completely and improve the recovery rate of each element, especially the Fe element.
[0073] Furthermore, in the first filtrate, the molar ratio of phosphate to pyrophosphate is 1:(0.45-0.49), so as to better form sodium ferric fluoropyrophosphate with higher phase purity during the subsequent calcination to obtain the positive electrode material, thereby improving its electrochemical performance.
[0074] Furthermore, in order to improve the removal effect of heavy metal ions and thereby improve the purity and electrochemical performance of the obtained positive electrode material, the ratio of the amount of the precipitant to the total amount of nickel ions, cobalt ions, copper ions and zinc ions in the first filtrate is preferably (1.2 to 1.5):1.
[0075] Furthermore, the reaction temperature of the second reaction is 40°C to 60°C, and the reaction time is 30min to 60min. Preferably, the pH value of the second reaction is 1.8 to 2.5. The selection of the above reaction conditions is conducive to more effectively removing impure metal ions, improving the purity of the obtained positive electrode material and the cycle stability of its corresponding sodium ion battery.
[0076] Furthermore, in order to more efficiently precipitate anions such as iron, phosphate and pyrophosphate in the second filtrate, improve the purity of the obtained third filtrate, and more effectively make the obtained positive electrode material have fewer impurities, higher phase purity and better electrochemical performance, the endpoint pH value of the third reaction is preferably 2.8 to 3.2. And, in the third reaction, after reaching the endpoint pH value of the third reaction, continue the reaction for 30 minutes to 60 minutes.
[0077] Furthermore, the ratio of the amount of iron in the ferrous source (such as ferrous acetate) to the amount of pyrophosphate in the second filtrate is (0.95-0.98):1, thereby more effectively reducing the generation of by-products and improving the phase purity of the positive electrode material.
[0078] Further, the adsorption treatment includes: adding the third filtrate to the ion exchange resin for adsorption treatment until Li + Concentration <100ppm. The present application realizes the separation and adsorption of lithium elements in waste lithium iron phosphate materials through ion exchange resin, so that the residual amount of lithium elements in the adsorption residual liquid is less and the lithium element recovery rate is higher. And the adsorption residual liquid with extremely low lithium content obtained by separation and adsorption treatment can be recovered as a solution, mixed with the third filter residue, sodium source, phosphorus source and fluorine source to obtain a mixed slurry, so as to prepare a positive electrode material. The obtained positive electrode material has fewer impurities, higher purity and phase purity, and better electrochemical performance.
[0079] Furthermore, in the adsorption treatment, before adding the third filtrate to the ion exchange resin, the pH value of the third filtrate is adjusted to 5-7, and the temperature of the third filtrate is maintained at 55°C-65°C, so that the ion exchange resin can achieve the best adsorption effect on lithium ions in the third filtrate.
[0080] Furthermore, when the third filtrate is added with ion exchange resin for adsorption treatment, the temperature of the adsorption treatment is 55° C. to 65° C., so as to maintain the adsorption effect of the ion exchange resin on the lithium ions in the third filtrate.
[0081] Furthermore, the ion exchange resin is a cation exchange resin, preferably HPL900 or GC-18. Also, when the ion exchange resin adsorbs lithium to a lithium content of 4 g / L to 6 g / L, 2 mol / L to 4 mol / L sulfuric acid is added to the ion exchange resin for elution, and the eluate obtained by elution is precipitated to recover the lithium element, and the regenerated ion exchange resin after elution can be reused.
[0082] Furthermore, in the mixed slurry, the ratio of the amount of Na, Fe, P and F is (5.02-5.05):3:(4.02-4.05):(1.01-1.05). The above amount ratio of substances obtained through a large number of experiments, combined with grinding and drying, forms a positive electrode material with higher phase purity, better morphology and better electrochemical performance after calcination.
[0083] In order to further improve the crystal phase purity, crystallinity and stability of the obtained positive electrode material, the calcination holding temperature is 550°C to 650°C, the calcination holding time is 10h to 13h. Preferably, the calcination heating rate is 60°C / h to 120°C / h.
[0084] In some embodiments, the sodium source may be sodium citrate and / or sodium gluconate, the phosphorus source may be phosphoric acid and / or diammonium phosphate, and the fluoride source may be one or more of ammonium fluoride, hydrogen fluoride and sodium fluoride.
[0085] During the grinding process of the mixed slurry, it is preferred to grind the slurry to a particle size of 100 nm to 200 nm, and sodium hexadecylbenzene sulfonate can be added as a dispersant during the grinding process. The amount of the dispersant added can be 1% to 3% of the total weight of the mixed slurry.
[0086] In the spray drying process, the particle size of the spray-dried material is preferably 3 μm to 8 μm, and the moisture content is less than 0.5%.
[0087] During the calcination process, a roller furnace can be used for calcination. In some embodiments, nitrogen is introduced during the calcination process for atmosphere protection. At the same time, the oxygen content in the insulation section is maintained below 2ppm, the CO content is maintained below 100ppm, the CO2 content is maintained below 500ppm, and the humidity is maintained below 2%. The material is cooled to a temperature of ≤100°C after sintering before discharging.
[0088] In some embodiments, the calcined material is screened, iron removed and packaged to obtain the positive electrode material. Preferably, the screening is performed using a 100-200 mesh ultrasonic vibration screen, and the packaging process is performed in a constant temperature and humidity room to control the moisture content of the product to ≤600ppm.
[0089] The third aspect of the present application provides a positive electrode sheet, which includes the above-mentioned positive electrode material, or the positive electrode material prepared by the above-mentioned method for preparing the positive electrode material. Because the positive electrode material obtained in the present application has a better morphology, higher phase purity, and less internal impurities, the corresponding positive electrode sheet also has better electrochemical performance.
[0090] The fourth aspect of the present application provides a sodium ion battery, which includes the above-mentioned positive electrode plate. Because the above-mentioned sodium iron fluoropyrophosphate positive electrode material obtained in the present application has good microscopic morphology and extremely high phase purity, when it is used as a positive electrode plate component in a sodium ion battery, the obtained sodium ion battery also has comprehensively improved electrochemical performance, especially the first discharge capacity and cycle stability.
[0091] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0092] Unless otherwise defined, all professional terms used below have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this application.
[0093] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0094] 1. Preparation method
[0095] Example 1
[0096] Preparation method of positive electrode material based on waste lithium iron phosphate positive electrode material:
[0097] 1. Dissolve the waste lithium iron phosphate material in an alkaline solution (alkaline agent), the mass ratio of the waste lithium iron phosphate material to the alkaline solution is 1:4, the alkaline solution is a sodium hydroxide solution, and the concentration of the alkaline solution is 4 mol / L. Stop the reaction after dissolving until the aluminum content in the filter residue is less than 0.1%, filter, and obtain a pretreatment filtrate and a pretreatment filter residue. Pass carbon dioxide into the obtained pretreatment filtrate to obtain aluminum hydroxide precipitate and filtrate. The aluminum hydroxide precipitate and the filtrate after filtering out the aluminum hydroxide precipitate are tested, and the results are shown in Table 1.
[0098] Table 1
[0099]
[0100] 2. Add 4 mol / L pyrophosphoric acid to the pretreatment residue for the first reaction. The first reaction temperature is 80°C, the first reaction time is 1.5 h, and filter to obtain a first filtrate and a first residue. The molar ratio of phosphate to pyrophosphoric acid in the first filtrate is 1:0.48.
[0101] 3. Add sodium sulfide (precipitant) to the first filtrate obtained to carry out a second reaction. The amount of sodium sulfide added to the first filtrate is 1.4 times the total amount of nickel, cobalt, copper and zinc ions in the first filtrate. The second reaction temperature is 50° C., the second reaction time is 50 min, and the pH value of the reaction process is maintained at 2.1. After the heavy metals are precipitated by the reaction, the second filtrate and the second filter residue are obtained by filtering.
[0102] 4. Add sodium hydroxide (pH regulator), ferrous acetate (ferrous source) and an oxidant to the second filtrate obtained to carry out a third reaction. The molar ratio of the added ferrous acetate to the pyrophosphate in the second filtrate is 0.98:1. Add sodium hydroxide to adjust the pH value of the solution. The concentration of the sodium hydroxide solution is 8 mol / L, the concentration of the ferrous acetate solution is 2 mol / L, and the oxidant is hydrogen peroxide with a concentration of 9 mol / L. Stir the reaction until the endpoint pH value is 3.2. Continue stirring for the third reaction time of 45 min and then filter to obtain a third filtrate and a third filter residue.
[0103] 5. The third filtrate was added to HPL900 type weak acid cation exchange resin for adsorption, and its saturated adsorption capacity was 5.5 g / L (the amount of lithium ions adsorbed by 1L ion exchange resin). Before the ion exchange resin treatment, sodium hydroxide was added to adjust the pH value of the third filtrate to 6.2, and then the temperature of the third filtrate after pH adjustment was raised to 60°C. The lithium content before entering the ion exchange resin was 12.24 g / L, and the adsorption temperature was 60°C. After 5 consecutive ion exchange resin columns, the lithium ion concentration was reduced to 67 ppm to obtain an adsorption residual liquid. The adsorption residual liquid and the third filter residue were mixed and slurried to obtain a slurry, and the concentrations of Na, Fe, P and F therein were detected by sampling, and the molar ratio of the above elements was measured to be 0.45:3:4:0.0006; a sodium source (a mixture of sodium acetate and sodium citrate in a mass ratio of 5:5), a phosphorus source (ammonium dihydrogen phosphate) and a fluorine source (sodium fluoride) were respectively added to the slurry to obtain a mixed slurry, and the molar ratio of Na, Fe, P and F in the mixed slurry was maintained at 5.03:3:4.04:1.03.
[0104] 6. The mixed slurry is ground to a particle size of 130 nm for the solid component of the mixed slurry. A dispersant is added during the grinding process. The dispersant is sodium hexadecylbenzene sulfonate, and the amount added is 2.1% of the mass of the mixed slurry. The ground mixed slurry is spray-dried and nitrogen is introduced for atmosphere protection. The obtained spray-dried material has a particle size of 6.2 μm and a moisture content of less than 0.5%. The spray-dried material is calcined in a roller furnace. The heating rate of the heating section during the calcination process is 100°C / h. The temperature is raised to 600°C and kept warm for 12 hours. The oxygen content in the heat preservation section is maintained at less than 2ppm, the CO content is less than 100ppm, the CO2 content is less than 500ppm, and the humidity is ≤2% by adjusting the nitrogen introduction amount. After the calcination is completed, the material is cooled to a temperature of ≤100°C after sintering and then discharged. The discharged material is screened using a 100-mesh ultrasonic vibration screen. The iron removal and packaging process are carried out in a constant temperature and humidity room. The moisture content of the final product is controlled to be ≤600ppm to obtain the positive electrode material.
[0105] 7. After the ion exchange resin adsorbs lithium, when the lithium content in the ion exchange resin is 5.3 g / L, 3 mol / L sulfuric acid is added for elution. The eluate after elution is precipitated to recover lithium to obtain lithium carbonate with a purity higher than 98.5% (mass fraction). The regenerated ion exchange resin after elution can be recycled.
[0106] The obtained positive electrode material was subjected to XRD test and the Figure 1 . The obtained spectrum shows that the positive electrode material includes Na 5.03 Fe3(PO4) 2.0 (P2O7) 1.02 F 1.03 The mass fraction of sodium iron phosphate impurities in the positive electrode material is 0.14%.
[0107] The SEM image of the obtained positive electrode material is shown in Figure 1 , XRD spectrum see Figure 2 .
[0108] At the same time, in the XRD spectrum of the positive electrode material, the main peak height H1 of sodium ferric phosphate fluoropyrophosphate and the main peak height H2 of the sodium ferric phosphate impurity satisfy H2 / H1=0.2% (wherein the peak position of the main peak height H2 of the sodium ferric phosphate impurity is shown as the dotted line, and the main peak height H1 of sodium ferric phosphate fluoropyrophosphate is already marked).
[0109] Example 2
[0110] Preparation method based on waste lithium iron phosphate positive electrode material:
[0111] 1. Dissolve the waste lithium iron phosphate material in an alkaline solution (alkaline agent), and then filter to obtain a pretreatment filtrate and a pretreatment filter residue. The mass ratio of the waste lithium iron phosphate material to the alkaline solution is 1:3. The alkaline solution is a sodium hydroxide solution. The concentration of the alkaline solution is 5 mol / L. Stop the reaction after the aluminum content in the filter residue is less than 0.1%. Pass carbon dioxide into the pretreatment filtrate to obtain aluminum hydroxide precipitate and filtrate;
[0112] 2. Add 5 mol / L pyrophosphoric acid to the pretreatment residue for the first reaction. The first reaction temperature is 70°C, the first reaction time is 2 h, and the first filtrate and the first residue are obtained. The molar ratio of phosphate to pyrophosphoric acid in the first filtrate is 1:0.45.
[0113] 3. Add sodium sulfide (precipitant) to the first filtrate obtained to carry out a second reaction. The amount of sodium sulfide added to the first filtrate is 1.2 times the total amount of nickel, cobalt, copper and zinc ions in the first filtrate. The second reaction temperature is 60° C., the second reaction time is 60 min, and the pH value of the reaction process is maintained at 2.5. After the heavy metals are precipitated by the reaction, the second filtrate and the second filter residue are obtained by filtering.
[0114] 4. Add sodium hydroxide (pH regulator), ferrous acetate (ferrous source) and ozone to the second filtrate obtained to carry out a third reaction. The molar ratio of the added ferrous acetate to the pyrophosphate in the second filtrate is 0.95:1, and the concentration of the ferrous acetate solution is 1.5 mol / L. First, add ozone so that 50% of the ferrous iron in the solution is oxidized to trivalent iron, and then add a sodium hydroxide solution with a concentration of 10 mol / L. Stir the reaction until the endpoint pH value is 2.8, continue stirring for the third reaction time of 60 min, and then filter to obtain a third filtrate and a third filter residue.
[0115] 5. The third filtrate is added to GC-18 weakly acidic cation exchange resin for adsorption until the lithium ion concentration is reduced to 100 pm to obtain an adsorption residual liquid. The adsorption residual liquid and the third filter residue are mixed and slurried to obtain a slurry, and the concentrations of Na, Fe, P and F therein are detected by sampling; sodium gluconate (sodium source), phosphoric acid (phosphorus source) and ammonium fluoride (fluorine source) are respectively added to the slurry to obtain a mixed slurry, and the molar ratio of Na, Fe, P and F in the mixed slurry is maintained at 5.02:3:4.02:1.01.
[0116] 6. The mixed slurry is ground to a particle size of 100 nm for the solid component of the mixed slurry. A dispersant is added during the grinding process. The dispersant is sodium hexadecylbenzene sulfonate, and the amount added is 1% of the mass of the mixed slurry. The ground mixed slurry is spray dried and nitrogen is introduced for atmosphere protection. The obtained spray dried material has a particle size of 3 μm and a moisture content of less than 0.5%. The spray dried material is calcined in a roller furnace. The heating rate of the heating section during the calcination process is 60°C / h. The temperature is raised to 550°C and kept for 13 hours. The oxygen content in the heat preservation section is maintained below 2ppm, the CO content is below 100ppm, the CO2 content is below 500ppm, and the humidity is ≤2% by adjusting the nitrogen introduction amount. After the calcination is completed, the material is cooled to a temperature of ≤100°C after sintering and then discharged. The discharged material is screened using a 100-mesh ultrasonic vibration screen. The iron removal and packaging process are carried out in a constant temperature and humidity room. The moisture content of the final product is controlled to be ≤600ppm to obtain the positive electrode material.
[0117] 7. After the ion exchange resin adsorbs lithium, when the lithium content in the ion exchange resin is 4g / L, 4mol / L sulfuric acid is added for elution. The eluate after elution is precipitated to recover lithium, and the regenerated ion exchange resin after elution is returned for use.
[0118] The obtained positive electrode material was subjected to XRD test, and the results are shown in Figure 2 . The obtained spectrum shows that the positive electrode material includes a molecular formula of Na 5.02 Fe3(PO4) 2.0 (P2O7) 1.01 F 1.01 The mass fraction of sodium iron phosphate impurities in the positive electrode material is 0.23%.
[0119] At the same time, in the XRD spectrum of the positive electrode material, the main peak height H1 of sodium ferric phosphate fluoropyrophosphate and the main peak height H2 of the sodium ferric phosphate impurity satisfy H2 / H1=0.4% (the peak position of the main peak height H2 of the sodium ferric phosphate impurity is shown by the dotted line, and the main peak height H1 of sodium ferric phosphate fluoropyrophosphate is marked).
[0120] Example 3
[0121] Preparation method based on waste lithium iron phosphate positive electrode material:
[0122] 1. Dissolve the waste lithium iron phosphate material in an alkaline solution (alkaline agent), and then filter to obtain a pre-treatment filtrate and a pre-treatment filter residue. The mass ratio of the waste lithium iron phosphate material to the alkaline solution is 1:5. The alkaline solution is a sodium hydroxide solution. The concentration of the alkaline solution is 5 mol / L. The reaction is stopped after the aluminum content in the filter residue is less than 0.1%. Carbon dioxide is introduced into the pre-treatment filtrate to obtain aluminum hydroxide precipitate and filtrate;
[0123] 2. Add 3 mol / L pyrophosphoric acid to the pretreated residue for a first reaction. The first reaction temperature is 90° C., the first reaction time is 1 h, and the mixture is filtered to obtain a first filtrate and a first residue. The molar ratio of phosphate to pyrophosphoric acid in the first filtrate is 1:0.49.
[0124] 3. Add sodium sulfide (precipitant) to the first filtrate obtained to carry out a second reaction. The amount of sodium sulfide added to the first filtrate is 1.5 times the total amount of nickel, cobalt, copper and zinc ions in the first filtrate. The second reaction temperature is 40° C., the second reaction time is 30 min, and the pH value of the reaction process is maintained at 1.8. After the heavy metals are precipitated by the reaction, the second filtrate and the second filter residue are obtained by filtering.
[0125] 4. Add sodium hydroxide (pH regulator), ferrous acetate (ferrous source) and an oxidant to the second filtrate obtained to carry out a third reaction. The molar ratio of the added ferrous acetate to the pyrophosphate in the second filtrate is 0.98:1. Add sodium hydroxide to adjust the pH value of the solution. The concentration of the sodium hydroxide solution is 10 mol / L, and the concentration of the ferrous acetate solution is 2.5 mol / L. Stir the reaction until the endpoint pH value is 3.2, and continue the third reaction time for 30 min to obtain a third filtrate and a third filter residue.
[0126] 5. Add the third filtrate to HPL900 weakly acidic cation exchange resin for adsorption until the lithium ion concentration therein is reduced to 100 pm, and obtain an adsorption residual liquid. Mix the adsorption residual liquid and the third filter residue to obtain a slurry, and take samples to detect the concentrations of Na, Fe, P and F therein; add sodium gluconate (sodium source), ammonium dihydrogen phosphate (phosphorus source) and hydrogen fluoride (fluorine source) to the slurry to obtain a mixed slurry, and maintain the molar ratio of Na, Fe, P and F in the mixed slurry at 5.05:3:4.05:1.05.
[0127] 6. The mixed slurry is ground to a particle size of 200 nm for the solid component of the mixed slurry. A dispersant is added during the grinding process. The dispersant is sodium hexadecylbenzene sulfonate, and the amount added is 3% of the mass of the mixed slurry. The ground mixed slurry is spray dried and nitrogen is introduced for atmosphere protection. The obtained spray dried material has a particle size of 8 μm and a moisture content of less than 0.5%. The spray dried material is calcined in a roller furnace. The heating rate of the heating section during the calcination process is 120°C / h. The temperature is raised to 650°C and kept for 10 hours. The oxygen content in the heat preservation section is maintained below 2ppm, the CO content is below 100ppm, the CO2 content is below 500ppm, and the humidity is ≤2% by adjusting the nitrogen introduction amount. After the calcination is completed, the material is cooled to a temperature of ≤100°C after sintering and then discharged. The discharged material is screened using a 200-mesh ultrasonic vibration screen. The iron removal and packaging process are carried out in a constant temperature and humidity room. The moisture content of the final product is controlled to be ≤600ppm to obtain the positive electrode material.
[0128] 7. After the ion exchange resin adsorbs lithium, when the lithium content in the ion exchange resin reaches 6g / L, 4mol / L sulfuric acid is added for elution. The eluate after elution is precipitated to recover lithium, and the regenerated ion exchange resin after elution is returned for use.
[0129] The obtained positive electrode material was subjected to XRD test, and the results are shown in Figure 2 . The obtained spectrum shows that the positive electrode material includes Na 5.05 Fe3(PO4) 2.01 (P2O7) 1.01 F 1.05The sodium ferric phosphate with a molecular formula of NaFePO4 is contained in the positive electrode material, and the mass fraction of the sodium ferric phosphate impurity is 0.21%.
[0130] At the same time, in the XRD spectrum of the positive electrode material, the main peak height H1 of sodium ferric phosphate fluoropyrophosphate and the main peak height H2 of the sodium ferric phosphate impurity satisfy H2 / H1=0.3% (the peak position of the main peak height H2 of the sodium ferric phosphate impurity is shown by the dotted line, and the main peak height H1 of sodium ferric phosphate fluoropyrophosphate is marked).
[0131] Example 4
[0132] Preparation method based on waste lithium iron phosphate positive electrode material:
[0133] The difference between this embodiment and embodiment 1 is only in step 1 and step 2, specifically:
[0134] 1. Dissolve the waste lithium iron phosphate material in an alkaline solution (alkaline agent), the mass ratio of the waste lithium iron phosphate material to the alkaline solution is 1:2, the alkaline solution is a sodium hydroxide solution, and the concentration of the alkaline solution is 4 mol / L. Stop the reaction after dissolving until the aluminum content in the filter residue is less than 0.1%, filter, and obtain a pretreated filtrate and a pretreated filter residue.
[0135] 2. Add 2 mol / L pyrophosphoric acid to the pretreated residue for a first reaction. The first reaction temperature is 100° C., the first reaction time is 0.5 h, and a first filtrate and a first residue are obtained. The molar ratio of phosphate to pyrophosphoric acid in the first filtrate is 1:0.5.
[0136] The remaining steps are exactly the same as those in Example 1.
[0137] Example 5
[0138] Preparation method based on waste lithium iron phosphate positive electrode material:
[0139] The difference between this embodiment and embodiment 1 is only in step 1 and step 2, specifically:
[0140] 1. Dissolve the waste lithium iron phosphate material in an alkaline solution (alkaline agent), the mass ratio of the waste lithium iron phosphate material to the alkaline solution is 1:6, the alkaline solution is a sodium hydroxide solution, and the concentration of the alkaline solution is 4 mol / L. Stop the reaction after dissolving until the aluminum content in the filter residue is less than 0.1%, filter, and obtain a pretreated filtrate and a pretreated filter residue.
[0141] 2. Add 6 mol / L pyrophosphoric acid to the pretreatment residue for the first reaction. The first reaction temperature is 60°C, the first reaction time is 2.5 h, and filter to obtain a first filtrate and a first residue. The molar ratio of phosphate to pyrophosphoric acid in the first filtrate is 1:0.4.
[0142] The remaining steps are exactly the same as those in Example 1.
[0143] Example 6
[0144] Preparation method based on waste lithium iron phosphate positive electrode material:
[0145] The difference between this embodiment and embodiment 1 is only in step 3, specifically:
[0146] 3. Add sodium sulfide (precipitant) to the first filtrate obtained to carry out a second reaction. The amount of sodium sulfide added to the first filtrate is 1 times the total amount of nickel, cobalt, copper and zinc ions in the first filtrate. The second reaction temperature is 65° C., the second reaction time is 25 min, and the pH value of the reaction process is maintained at 1.5. After the heavy metals are precipitated by the reaction, the second filtrate and the second filter residue are obtained by filtering.
[0147] The remaining steps are exactly the same as those in Example 1.
[0148] Example 7
[0149] Preparation method based on waste lithium iron phosphate positive electrode material:
[0150] The difference between this embodiment and embodiment 1 is only in step 3, specifically:
[0151] 3. Add sodium sulfide (precipitant) to the first filtrate obtained to carry out a second reaction. The amount of sodium sulfide added to the first filtrate is twice the total amount of nickel, cobalt, copper and zinc ions in the first filtrate. The second reaction temperature is 35° C., the second reaction time is 65 min, and the pH value of the reaction process is maintained at 3.0. After the heavy metals are precipitated by the reaction, the second filtrate and the second filter residue are obtained by filtering.
[0152] The remaining steps are exactly the same as those in Example 1.
[0153] Example 8
[0154] Preparation method based on waste lithium iron phosphate positive electrode material:
[0155] The difference between this embodiment and embodiment 1 is only in step 5 and step 6, specifically:
[0156] 5. The third filtrate was added to HPL900 type weak acid cation exchange resin for adsorption, and its saturated adsorption capacity was 5.5 g / L (lithium ion content adsorbed by 1L ion exchange resin). Before the ion exchange resin treatment, sodium hydroxide was added to adjust the pH value of the third filtrate to 6.2, and then the temperature of the third filtrate after pH adjustment was raised to 60°C. The lithium content before entering the ion exchange resin was 12.24 g / L, and the adsorption temperature was 60°C. After 5 consecutive ion exchange resin columns, the lithium ion concentration was reduced to 67 ppm to obtain an adsorption residual liquid. The adsorption residual liquid and the third filter residue are mixed and slurried to obtain a slurry, and samples are taken to detect the concentrations of Na, Fe, P and F therein; a sodium source (a mixture of sodium acetate and sodium citrate in a mass ratio of 5:5), a phosphorus source (ammonium dihydrogen phosphate) and a fluorine source (sodium fluoride) are respectively added to the slurry to obtain a mixed slurry, and the molar ratio of Na, Fe, P and F in the mixed slurry is maintained at 5.00:3:4.035:1.03.
[0157] 6. The mixed slurry is ground to a particle size of 130 nm for the solid component of the mixed slurry. A dispersant is added during the grinding process. The dispersant is sodium hexadecylbenzene sulfonate, and the amount added is 2.1% of the mass of the mixed slurry. The ground mixed slurry is spray-dried and nitrogen is introduced for atmosphere protection. The obtained spray-dried material has a particle size of 6.2 μm and a moisture content of less than 0.5%. The spray-dried material is calcined in a roller furnace. The heating rate of the heating section during the calcination process is 50°C / h. The temperature is raised to 500°C and kept warm for 14 hours. The oxygen content in the heat preservation section is maintained at less than 2ppm, the CO content is less than 100ppm, the CO2 content is less than 500ppm, and the humidity is ≤2% by adjusting the nitrogen introduction amount. After the calcination is completed, the material is cooled to a temperature of ≤100°C after sintering and then discharged. The discharged material is screened using a 100-mesh ultrasonic vibration screen. The iron removal and packaging process are carried out in a constant temperature and humidity room. The moisture content of the final product is controlled to be ≤600ppm to obtain the positive electrode material.
[0158] The remaining steps are exactly the same as those in Example 1.
[0159] Example 9
[0160] Preparation method based on waste lithium iron phosphate positive electrode material:
[0161] The difference between this embodiment and embodiment 1 is only in step 5 and step 6, specifically:
[0162] 5. The third filtrate was added to HPL900 type weak acid cation exchange resin for adsorption, and its saturated adsorption capacity was 5.5 g / L (lithium ion content adsorbed by 1L ion exchange resin). Before the ion exchange resin treatment, sodium hydroxide was added to adjust the pH value of the third filtrate to 6.2, and then the temperature of the third filtrate after pH adjustment was raised to 60°C. The lithium content before entering the ion exchange resin was 12.24 g / L, and the adsorption temperature was 60°C. After 5 consecutive ion exchange resin columns, the lithium ion concentration was reduced to 67 ppm to obtain an adsorption residual liquid. The adsorption residual liquid and the third filter residue are mixed and slurried to obtain a slurry, and samples are taken to detect the concentrations of Na, Fe, P and F therein; a sodium source (a mixture of sodium acetate and sodium citrate in a mass ratio of 5:5), a phosphorus source (ammonium dihydrogen phosphate) and a fluorine source (sodium fluoride) are respectively added to the slurry to obtain a mixed slurry, and the molar ratio of Na, Fe, P and F in the mixed slurry is maintained at 5.035:3:4.00:1.03.
[0163] 6. The mixed slurry is ground to a particle size of 130 nm for the solid component of the mixed slurry. A dispersant is added during the grinding process. The dispersant is sodium hexadecylbenzene sulfonate, and the amount added is 2.1% of the mass of the mixed slurry. The ground mixed slurry is spray-dried and nitrogen is introduced for atmosphere protection. The particle size of the spray-dried material obtained is 6.2 μm and the moisture content is less than 0.5%. The spray-dried material is calcined in a roller furnace. The heating rate of the heating section during the calcination process is 150°C / h. The temperature is raised to 700°C and kept warm for 9 hours. The oxygen content in the heat preservation section is maintained at less than 2ppm, the CO content is less than 100ppm, the CO2 content is less than 500ppm, and the humidity is ≤2% by adjusting the nitrogen introduction amount. After the calcination is completed, the material is cooled to a temperature of ≤100°C after sintering and then discharged. The discharged material is screened using a 100-mesh ultrasonic vibration screen. The iron removal and packaging process are carried out in a constant temperature and humidity room. The moisture content of the final product is controlled to be ≤600ppm to obtain the positive electrode material.
[0164] The remaining steps are exactly the same as those in Example 1.
[0165] Comparative Example 1
[0166] Preparation method based on waste lithium iron phosphate positive electrode material:
[0167] The difference between this comparative example and Example 1 is that sodium fluoride is not added to the slurry obtained by mixing the adsorption residual liquid and the third filter residue, and a sodium source (a mixture of sodium acetate and sodium citrate, with a mass ratio of 5:5) and a phosphorus source (ammonium dihydrogen phosphate) are added to the slurry to obtain a mixed slurry, and the molar ratio of Na, Fe and P in the mixed slurry is maintained at 4.03:3:4.04. The obtained positive electrode material includes a molecular formula of Na 4.03 Fe3(PO4)1.95 (P2O7) 1.045 of sodium ferric pyrophosphate.
[0168] 2. Test Method
[0169] 1. Physical and chemical performance test of positive electrode materials
[0170] Iron dissolution test: add 1g of the sample to be tested into 100mL of 0.1mol / L hydrogen fluoride-ethanol solution, stir and dissolve at 45°C for 30min, then filter and measure the iron content in the filtrate, which is the iron dissolution amount.
[0171] Free sodium content: determined by potentiometric titration.
[0172] Magnetic substance content: collected by magnet, dissolved in aqua regia, and tested on an atomic absorption spectrometer.
[0173] Sphericity: Sphericity analyzer and SEM were used for testing.
[0174] Powder resistivity: tested using the four-probe method at a pressure of 10 MPa.
[0175] Particle size (D50 particle size): GB / T 19077, particle size analysis by laser diffraction method.
[0176] Specific surface area (BET): The gas adsorption BET method is used to determine the specific surface area of solid substances.
[0177] Tap density: GB / T 5162-2021, Determination of tap density of powders.
[0178] Compacted density: GB / T 24533, Determination of compacted density of powders.
[0179] 2. Button battery performance test
[0180] The positive electrode materials obtained in each embodiment and comparative example were mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 85:7:8, respectively, and coated on aluminum foil. Then, a pole piece was prepared with a compaction density of 2.2 g / mL, a sodium sheet was used for the negative electrode, and the electrolyte was a 1 mol / L sodium perchlorate solution. The batteries were assembled into button cells, and their first charge specific capacity, first discharge specific capacity, and first discharge median voltage at a rate of 0.2C were tested; the first discharge specific capacity at 1C; and the capacity retention rate after 560 cycles at a rate of 1C were tested.
[0181] The test results of the above tests are shown in Table 2, Table 3 and Table 4 respectively.
[0182] Table 2
[0183]
[0184]
[0185] Table 3
[0186]
[0187] Table 4
[0188]
[0189] III. Analysis of test results of various embodiments and comparative examples
[0190] From the results in Table 1 above, it can be seen that the present application further precipitates the pre-treated filtrate obtained by alkali dissolution of the discarded lithium iron phosphate positive electrode material to obtain a relatively high purity aluminum hydroxide, which has a large BTE specific surface area and can be used as a catalyst carrier for recovery and application in the catalytic field. In addition, the residual filtrate obtained by the precipitation treatment of the pre-treated filtrate is mainly composed of sodium salt, which can be mixed with the third filter residue to supplement the sodium element.
[0191] From the results in Tables 2 to 4 above, it can be seen that the above embodiments of the present application achieve the preparation of a positive electrode material for a sodium ion battery with low impurity content, high purity and high sphericity, specifically:
[0192] By comparing Examples 1 to 9 with Comparative Example 1, it can be seen that the preparation method adopted in the present application introduces fluoride ions to obtain a positive electrode material having sodium iron phosphate fluoropyrophosphate, and its various performances are more superior. After further preparation of a sodium ion battery, the corresponding sodium ion battery exhibits higher first charge specific capacity, first discharge specific capacity, first discharge median voltage and long cycle stability, indicating that the positive electrode material provided by the present application has higher energy density, lower polarization and stronger stability.
[0193] Comparing Examples 1 to 3 with Examples 4 and 5, it can be seen that in the alkaline dissolution process, the preferred weight ratio of the alkaline solution to the waste lithium iron phosphate positive electrode material is (3 to 5): 1, and the concentration of the alkaline solution is 3 mol / L to 5 mol / L; in the first reaction process, the concentration of the pyrophosphoric acid solution used is preferably 3 mol / L to 5 mol / L, the molar ratio of phosphate to pyrophosphate is 1: (0.45 to 0.49), the first reaction temperature is controlled to 70°C to 90°C, and the first reaction time is controlled to 1h to 2h, which can effectively reduce the formation of sodium iron phosphate impurity phase, improve the sphericity of the obtained positive electrode material, and improve the electrochemical performance of the positive electrode material, especially the subsequent cycle stability of the prepared sodium ion battery.
[0194] Comparing Examples 1 to 3 with Examples 6 and 7, it can be seen that in the process of removing heavy metal ions in the second reaction, by preferably using sodium sulfide (precipitant) and the sum of the amounts of nickel ions, cobalt ions, copper ions and zinc ions in the first filtrate The ratio is (1.2-1.5): 1, the second reaction temperature is 40°C-60°C, the second reaction time is 30min-60min, and the pH value during the second reaction is controlled to be 1.8-2.5, which is beneficial to significantly improve the purity of the obtained positive electrode material, so that the corresponding sodium ion battery exhibits higher first charge specific capacity, first discharge specific capacity, first discharge median voltage and cycle stability.
[0195] By comparing Examples 1 to 3 with Examples 8 and 9, it can be seen that it is preferred to control the amount ratio of Na, Fe, P and F in the mixed slurry to (5.02-5.05):3:(4.02-4.05):(1.01-1.05), and control the calcination temperature during the calcination process to 550°C-650°C and the insulation time to 10h-13h, which is beneficial to effectively optimize the micromorphology and electrochemical properties of the obtained positive electrode material, and further improve the charge capacity, discharge capacity and cycle stability of the corresponding sodium ion battery.
[0196] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes sodium ferric phosphate fluoropyrophosphate, and the molecular formula of the sodium ferric phosphate fluoropyrophosphate is Na m Fe3(PO4) p (P2O7) q F w , among which, 5.02≤m≤5.05, 4.02≤p+2q≤4.05, 0.5p≤q≤0.55p, 1.01≤w≤1.05, 1.87≤p≤2.
05.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material further includes sodium iron phosphate, and the mass fraction of the sodium iron phosphate in the positive electrode material is ≤1.1%; In the XRD spectrum of the positive electrode material, the main peak height H1 of the sodium ferric phosphate fluoropyrophosphate and the main peak height H2 of the sodium ferric phosphate impurity satisfy: H2 / H1≤1.5%.
3. The positive electrode material according to claim 1 or 2, characterized in that The sphericity of the positive electrode material is 0.94-0.
99.
4. A method for preparing a positive electrode material, characterized in that: The preparation method of the positive electrode material comprises: Provide discarded lithium iron phosphate cathode materials; Dissolving the discarded lithium iron phosphate positive electrode material to obtain a pre-treated filter residue; The pre-treatment filter residue is mixed with a pyrophosphoric acid solution to obtain a first filtrate; The first filtrate is mixed with a precipitant to obtain a second filtrate; The second filtrate is mixed with a pH regulator, a ferrous source, and an oxidant to obtain a third filtrate and a third filter residue; performing adsorption treatment on the third filtrate to obtain an adsorption residual liquid; The adsorption residual liquid, the third filter residue, a sodium source, a phosphorus source and a fluorine source are mixed to obtain a mixed slurry; The mixed slurry is ground, dried and calcined in sequence to obtain the positive electrode material.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: In the step of dissolving the discarded lithium iron phosphate positive electrode material to obtain the pre-treated filter residue, an alkaline agent is used to dissolve the discarded lithium iron phosphate positive electrode material; and / or, The step of mixing the pre-treated filter residue with the pyrophosphoric acid solution to obtain the first filtrate comprises: mixing the pre-treated filter residue with the pyrophosphoric acid solution, reacting at a first reaction temperature for a first time, and then performing a first solid-liquid separation treatment to obtain the first filtrate; and / or, The step of mixing the first filtrate with the precipitant to obtain the second filtrate comprises: mixing the first filtrate with the precipitant, reacting at a second reaction temperature for a second time, and performing a second solid-liquid separation treatment to obtain the second filtrate; and / or, The step of mixing the second filtrate with the pH regulator, the ferrous source and the oxidant to obtain the third filtrate and the third filter residue comprises: mixing the second filtrate with the pH regulator, the ferrous source and the oxidant, and performing a third reaction time after reaching a third reaction endpoint pH value, and performing a third solid-liquid separation treatment to obtain the third filtrate and the third filter residue; and / or, The step of adsorption treatment includes: using ion exchange resin to adsorb and treat the third filtrate.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: The mass ratio of the alkaline agent to the waste lithium iron phosphate positive electrode material is (3-5):1; In the first filtrate, the molar ratio of phosphate to pyrophosphate is 1:(0.45-0.49); The ratio of the amount of the precipitant to the sum of the amounts of nickel ions, cobalt ions, copper ions and zinc ions in the first filtrate is (1.2-1.5):1; The ratio of the amount of the iron element in the ferrous source to the amount of the pyrophosphate in the second filtrate is (0.95-0.98):1; In the mixed slurry, the molar ratio of Na, Fe, P and F is (5.02-5.05):3:(4.02-4.05):(1.01-1.05).
7. The method for preparing the positive electrode material according to claim 6, characterized in that: The concentration of the alkali agent is 3 mol / L to 5 mol / L; The concentration of the pyrophosphate solution is 3 mol / L to 5 mol / L; In the pre-treated filter residue, the mass fraction of Al element is less than 0.1%; The adsorption residual liquid Li + Concentration <100ppm.
8. The method for preparing a positive electrode material according to any one of claims 5 to 7, characterized in that: The first reaction temperature is 70°C to 90°C, and the first reaction time is 1h to 2h; The second reaction temperature is 40°C to 60°C, and the second reaction time is 30min to 60min; The third reaction endpoint pH value is 2.8 to 3.2, and the third reaction time is 30 min to 60 min; The calcination temperature is 550° C. to 650° C., and the calcination holding time is 10 h to 13 h.
9. The method for preparing a positive electrode material according to any one of claims 5 to 7, characterized in that: The alkaline agent is a sodium hydroxide solution; The precipitant is selected from one or more of sodium sulfide, sodium bisulfide and sodium N,N-dimethyldithiocarbamate; The pH regulator is selected from one or more of sodium hydroxide, ammonia water, ammonium bicarbonate and ammonium carbonate; The ferrous source is selected from one or more of ferrous acetate, ferrous citrate and ferrous gluconate; The oxidant is selected from one or more of hydrogen peroxide, oxygen and ozone.
10. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 3, or the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 4 to 9.
11. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 10.